ANALISIS KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI TAHUN 2019–2022 - Junaidi Affan; Abdullah Satritama; Agung N Jati; Supriono, Supriono (Bajang Institute, 2024)
This research aims to examine the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover Ratio (TATO), Return On Assets (ROA), Return On Equity (ROE) on stock prices in listed energy sector companies on the Indonesian Stock Exchange in 2019 – 2022. This quantitative research uses 33 samples of companies listed on the Indonesian Stock Exchange. Data analysis was a multiple linear regression test, which was previously tested on classical assumptions with a significance level of 5%. The results of the t test show that partially the Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA) and Return On Equity (ROE) do not have a significant effect on stock prices. Meanwhile, Total Asset Turnover Ratio (TATO) has a significant effect on share prices. The F test results show that simultaneously CR, DER, TATO, ROA and ROE have a significant effect on share prices in energy sector mining companies listed on the Indonesia Stock Exchange 2019-2022.